Hydrogen sensing with high-performance via O- ion spillover at Pd single atoms stabilized SnO2 interface - Yunxiao Qian; Guorui Zhao; Changming Zhang; Shengjie Yin; Junwei Chen; Yuanyuan Luo; Zhengfeng Huang; Bo Liu; Guotao Duan (Communications Materials)
Abstract Developing hydrogen sensors with high performances is imperative for facilitating H2-related industries. Metal oxide semiconductor (MOS) based gas sensors are simple structures with low cost that are a promising approach for H2 detection. However, detection speed and selectivity of MOS-based sensors currently face great challenges. Herein, we design palladium single atoms (SAs) doped tin oxide (SnO2/Pdatom) for H2 detection. Actual sensing tests show an ultrafast response speed toward H2 (3s to 10 ppm H2), with detection limit of 50 ppb and superior selectivity. Using in-situ THz time-domain spectroscopy and density functional theory calculations, it proves that an extra energy band near Fermi level appeared in SnO2/Pdatom, and Pd SAs doped on SnO2 enhance signally concentration of free carrier in SnO2/Pdatom. Partial density of states reveals that coupling hybridization between Pd 4d orbital and O 2p orbital promotes electron injection from Pd 4d orbital into O π2p orbital, improving production of more O- ions on sensing surfaces. Consequentially, the sensing dynamics involving O- ions spillover at SnO2-Pdatom interface is discussed.